2010
DOI: 10.1007/s10895-010-0745-7
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorimetric Method for Determination and Validation of Cefixime in Pharmaceutical Preparations Through Derivatization with 2-Cyanoacetamide

Abstract: A simple, sensitive and accurate method has been developed for spectrofluorimetric determination of cefixime in pure form and pharmaceutical preparations. The method is based on the reaction of cefixime with 2-cyanoacetamide in the presence of 21% ammonia at 100 °C. The fluorescent reaction product showed maximum fluorescence intensity at λ 378 nm after excitation at λ 330 nm. The factors affecting the derivatization reaction were carefully studied and optimized. The fluorescence intensity versus concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The proposed reaction was carried out at different pH (6)(7)(8)(9)(10)(11), in order to select the most appropriate pH for complex formation. As shown in Figure 3, the relative fluorescence intensity increased by increasing the pH of the aqueous solution before reaching a maximum value in the pH range of 7.5 -8.5.…”
Section: Effect Of Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed reaction was carried out at different pH (6)(7)(8)(9)(10)(11), in order to select the most appropriate pH for complex formation. As shown in Figure 3, the relative fluorescence intensity increased by increasing the pH of the aqueous solution before reaching a maximum value in the pH range of 7.5 -8.5.…”
Section: Effect Of Phmentioning
confidence: 99%
“…The wide use of these antibiotics in modern antimicrobial therapy is due to their enhanced intrinsic microbiological activities and favorable safety profile. Chemically cephalosporin antibiotics are derived from the 7-aminocephalosporanic acid (7-ACA) which composed of a β-lactam ring fused with a dihydrothaizine ring (Table 1) Several methods have been reported for the quantitative determination of the cited cephalosporins including spectrophotometry [2][3][4][5][6][7][8], spectrofluorimetry [8][9][10][11][12][13][14], chemiluminescence [15], High performance liquid chromatography (HPLC) [16][17][18], Thin layer chromatography [19], capillary electrophoresis (CE) [20,21] and voltammetry [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…A thorough literature search revealed that some analytical methods have been used, including derivative spectrophotometric [8,9], capillary electrophoresis [10], chromatographic [11] and electroanalytical [12][13][14][15] techniques. Many of these methods involve a large number of complicated pretreatment steps for analysis and they require sophisticated and expensive instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, reported methods for the determination of OFL and CEF were in single or with other drugs in pharmaceutical preparations and biological fluids. Some of the other reported methods were spectrophotometry,[10] fluorometry,[111213] HPLC,[14151617181920212223] liquid chromatography tandem mass (LC-MS/MS)[2425] and capillary electrophoresis. [2627282930] Further, most of the reported methods for the determination of OFL and CEF in biological fluids involve tedious sample preparation procedures (liquid/liquid or solid phase extraction), low extraction yields and low sensitivity.…”
Section: Introductionmentioning
confidence: 99%